Both sides of the same coin: identifying the paradoxes of technology in brazilian online consumption - Dias Guerra Disconzi, Claudia Maria; Benedetti Corso, Kathiane; Valim Bandeira, Marina (Revista de Administração da UFSM, 2020)
The possibility of buying at any time of the day, researching prices and finding varied products are some of the advantages informed by online consumers. Despite the benefits, some disadvantages are also cited by these consumers, such as the impossibility of product experimentation, delay in delivery, difficulty in accessing websites and lack of security. With this, the possibility of paradoxical behavior among this type of consumer is verified. Therefore, this work aims to verify the presence of technology paradoxes in online consumer behavior. This is a descriptive-exploratory research, with a quantitative approach and a survey research method. A questionnaire was elaborated aiming to collect information regarding the profile of the online consumers interviewed and the characteristics of the purchase process, besides containing 28 statements referring to the 14 paradoxes of technology adapted from national surveys for consumption through the internet. A total of 263 respondents were obtained, where two pairs of paradoxes were present: Assimilation / Isolation and Planning / Improvisation.